PENGARUH PROMOSI DALAM MENINGKATKAN VOLUME PEMBIAYAAN IMPLAN DI BSM (STUDI KASUS BANK MANDIRI SYARIAH MUARA BUNGO) - Abdul Roni; Wahyudil Khotib; Tuti’ Nadhifah (Institut Agama Islam Syekh Maulana Qori Bangko, 2022)
This study aims to find out the marketing strategies carried out at independent Islamic banks in increasing the volume of implant financing, the extent to which promotional marketing strategies are able to increase the volume of implant financing at Muara Bungo Islamic banks. This research is a quantitative research. The data used are primary data, the data collection method used is using a questionnaire distributed to implant financing customers at the Sariah Mandiri bank in Muara Bungo as many as 91 respondents. The data analysis technique used a simple linear regression model. This study proves that promotion has an effect on increasing implant financing. This can be interpreted, in increasing the volume of independent Islamic bank implant financing products, it is necessary to implement an effective and efficient marketing strategy, one of which is by applying regular and consistent promotions so that what is promoted really has a positive impact on increasing the volume of implant financing at independent Islamic banks. in Muara Bungo.This study aims to find out the marketing strategies carried out at independent Islamic banks in increasing the volume of implant financing, the extent to which promotional marketing strategies are able to increase the volume of implant financing at Muara Bungo Islamic banks. This research is a quantitative research. The data used are primary data, the data collection method used is using a questionnaire distributed to implant financing customers at the Sariah Mandiri bank in Muara Bungo as many as 91 respondents. The data analysis technique used a simple linear regression model. This study proves that promotion has an effect on increasing implant financing. This can be interpreted, in increasing the volume of independent Islamic bank implant financing products, it is necessary to implement an effective and efficient marketing strategy, one of which is by applying regular and consistent promotions so that what is promoted really has a positive impact on increasing the volume of implant financing at independent Islamic banks. in Muara Bungo.